2020
DOI: 10.1186/s12974-020-01914-1
|View full text |Cite
|
Sign up to set email alerts
|

Microglial and peripheral immune priming is partially sexually dimorphic in adolescent mouse offspring exposed to maternal high-fat diet

Abstract: Background: Maternal nutrition is critical for proper fetal development. While increased nutrient intake is essential during pregnancy, an excessive consumption of certain nutrients, like fat, can lead to long-lasting detrimental consequences on the offspring. Animal work investigating the consequences of maternal high-fat diet (mHFD) revealed in the offspring a maternal immune activation (MIA) phenotype associated with increased inflammatory signals. This inflammation was proposed as one of the mechanisms cau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 121 publications
(212 reference statements)
0
59
0
Order By: Relevance
“…The microglial cytoplasm often contains long stretches of endoplasmic reticulum cisternae and lipidic inclusions (i.e., lipofuscin, lipid bodies or droplets, and lysosomes; to be described in the Organelles section below) ( Savage et al, 2018 ), which accumulate with aging. Microglia are frequently associated with pockets of extracellular space, contrary to other cell types in the mature healthy brain, and interact with both the vasculature and synapses ( Tremblay et al, 2010a , 2012 ; Bisht et al, 2016c ), as well as myelinated axons ( Lampron et al, 2015 ; Bordeleau et al, 2020 ).…”
Section: An Overview Of the Ultrastructural Identification Criteria Wmentioning
confidence: 99%
“…The microglial cytoplasm often contains long stretches of endoplasmic reticulum cisternae and lipidic inclusions (i.e., lipofuscin, lipid bodies or droplets, and lysosomes; to be described in the Organelles section below) ( Savage et al, 2018 ), which accumulate with aging. Microglia are frequently associated with pockets of extracellular space, contrary to other cell types in the mature healthy brain, and interact with both the vasculature and synapses ( Tremblay et al, 2010a , 2012 ; Bisht et al, 2016c ), as well as myelinated axons ( Lampron et al, 2015 ; Bordeleau et al, 2020 ).…”
Section: An Overview Of the Ultrastructural Identification Criteria Wmentioning
confidence: 99%
“…Diets with high levels of fats (regardless of their saturation state) can induce maternal overweight or obesity and diabetes, notably by sustaining a proinflammatory state, as demonstrated in diverse animal models of maternal high-fat diet (mHFD) ( Bolton and Bilbo, 2014 ; Castanon et al, 2015 ; Montalvo-Martínez et al, 2018 ). Beyond the increased fat mass, rodent models have also revealed an inflammatory state associated to mHFD (e.g., increase of cytokines IL-2, IL-4, IL-6) ( Castanon et al, 2015 ; Graf et al, 2016 ; Bordeleau et al, 2020 ; Kretschmer et al, 2020 ). Indeed, in vitro experiments confirmed that IL-6 can promote apoptosis of endothelial cells, thus impairing placental vasculature and leading to intrauterine growth restriction in vivo in a mHFD mouse model ( Kretschmer et al, 2020 ).…”
Section: Specific Nutrient Imbalance and Inflammationmentioning
confidence: 99%
“…As previously discussed, nutrients can influence inflammatory processes in the mother, which in turn can promote inflammation in the progeny. Indeed, animal models of mHFD have described changes of inflammatory mediators (e.g., CD11b, IL-6, NFκB, TLR4) in the brain across the lifespan: neonate ( Bilbo and Tsang, 2010 ; Graf et al, 2016 ), juvenile ( Bilbo and Tsang, 2010 ), adolescent ( Sasaki et al, 2014 ; Winther et al, 2018 ; Bordeleau et al, 2020 ), and adult ( Bilbo and Tsang, 2010 ; Sasaki et al, 2013 ) stages. These changes in gene expression seem to occur differently between ages, sexes, and brain regions.…”
Section: Implication For Pregnancy and The Progenymentioning
confidence: 99%
See 1 more Smart Citation
“…Their diversity is modulated by the genetic vulnerabilities, environmental challenges (e.g., stress, infection, pollution), lifestyle factors (e.g., diet, sleep, physical activity, alcohol, cannabis), peripheral comorbidities (e.g., asthma, colitis, arthritis) and other individual circumstances (e.g., exposure to nature, social support), thus tremendously increasing the variability (Hanamsagar and Bilbo, 2017 ; Tay et al, 2017a ; Savage and Tremblay, 2019 ; Madore et al, 2020 ). The non-neuronal cells further display differences in their CNS colonization, maturation, gene and protein expression, morphology, ultrastructure, function, and response to challenges between the sexes (Schwarz and Bilbo, 2012 ; Hui St.-Pierre et al, 2018 ; Nelson et al, 2019 ; Bordeleau et al, 2020 ; Yasuda et al, 2020 ). In the periphery, the concept of “immunobiography” has been formulated, to reflect the tremendous inter-individual differences in immune function cumulating during life, and propose the idea that the individual immune signature can inform in a very sensitive manner on the state of health or disease, and allow to predict the outcome of various treatment strategies (Del Giudice et al, 2017 ; Franceschi et al, 2017 ).…”
Section: The Individual Circumstances Increasing Variabilitymentioning
confidence: 99%